Dexamethasone-induced and estradiol-induced CREB activation and annexin 1 expression in CCRF-CEM lymphoblastic cells: evidence for the involvement of cAMP and p38 MAPK - M. Castro-caldas; A. F. Mendes; C. B. Duarte; M. C. F. Lopes (Hindawi Limited, 2003)
Aims: Annexin 1 (ANXA1), a member of the annexin family of calcium-binding and phospholipid-binding proteins, is a key mediator of the anti-inflammatory actions of steroid hormones. We have previously demonstrated that, in the human lymphoblastic CCRF-CEM cell line, both the synthetic glucocorticoid hormone, dexamethasone (Dex), and the estrogen hormone, 17β-estradiol (E2β), induce the synthesis of ANXA1, by a mechanism independent of the activation of their nuclear receptors. Recently, it was reported that the gene coding for ANXA1 contains a cAMP-responsive element (CRE). In this work, we investigated whether Dex and E2β were able to induce the activation of CRE binding proteins (CREB) in the CCRF-CEM cells. Moreover, we studied the intracellular signalling pathways involved in CREB activation and ANXA1 synthesis in response to Dex and E2β; namely, the role of cAMP and the p38 mitogen-activated protein kinase (MAPK).